KERAGAAN FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PENYULUH DI BALAI PENGKAJIAN TEKNOLOGI PERTANIAN - Fawzia Sulaiman; I Wayan Rusastra; Ahmad Subaidi (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2005)
Information of research results is an output and the main asset of the Assessment Institute of AgriculturalTechnology (AIAT). This information of research result needs to be formulated into easily understood information,using the most suitable media before being disseminated to various prospective users. In this respect, professionalswho deal with innovation transfer need to possess adequate knowledge and skills to ensure an efficient and effectiveflow of information from its source to intended audiences. The effort to increase the efficiency and effectiveness ofthe information flow of agricultural research result was the justification to merge the Institute for AgriculturalInformation (IAI) and AIAT. This institutional integration also brought the consequence of the involvement ofextentionists, who were the main professional staff of IAI, into the AIAT working system. After 10 years ofintegration, the increase of efficiency and effectiveness of innovation transfer at AIAT has not resulted as expected.This poor performance of innovation transfer is among others resulted from the unfavourable working condition ofextentionists in fulfilling their role and function within the AIAT working system. The objective of this study was toidentify constraints being faced by AIAT extentionists in fulfilling their role and function at AIAT. Results of thestudy indicated that the capacity of AIAT extentionists was a resultant or a product of existing policies and workingcondition within the Indonesian Agency for Agricultural Research and Development (IAARD) and AIAT, and at otherrelated agricultural institutions outside the IAARD. In this respect, AIAT extentionists were in agreement with almostall constraints being stated as hypotheses in this study. The AIAT extentionists indicated that their performance was aresultant of internal and external constraints within their working system as follows: (a) professional capacity of AIATextentionists, (b) professional performance of AIAT extentionists, (c) structural problems, (d) working facilities andsupporting administration, (e) external factors. Thus, efforts to increase the performance of AIAT extentionists shouldstart from implementing policies and various activities being needed to alleviate those five constraints mentionedabove.Key words: extentionist, innovation transfer, perceptionInformasi hasil penelitian dan pengkajian merupakan aset intelektual dan keluaran utama dari BPTP (BalaiPengkajian Teknologi Pertanian) yang perlu dikemas ke dalam “bahasa” yang mudah dimengerti sebelumdisampaikan kepada beerbagai khalayak penggunanya. Penyelenggara proses alih teknologi membutuhkanpengetahuan dan keterampilan yang memadai, agar alur teknologi ini dapat mengalir dengan efisien dan efektif darisumbernya kepada berbagai khalayak penggunanya. Hal ini melatarbelakangi pengintegrsian Bali Informasi Pertanianke dalam BPTP, yang juga menbawa konsekuensi masuknya penyuluh, yang merupakan staf fungsional utama di unitkerja eks BIP ke dalam sistem kerja BPTP. Setelah 10 tahun pengintegrasian BIP ke dalam BPTP, ternyatapeningkatan efisiensi dan efektivitas sistem alih inovasi pertanian belum seperti yang diharapkan. Penyebabnya antaralain kurang kondusifnya pelaksanaan tugas pokok dan fungsi penyuluh BPTP. Dengan demikian, perlu adanyaidentifikasi kendala yang dihadapi penyuluh BPTP dalam pelaksanaan tugas pokok dan fungsinya. Tujuan pengkajianini adalah untuk mengidentifikasi kendala yang dihadapi penyuluh BPTP dalam melaksanakan tugas pokok danfungsinya di BPTP. Hasil kajian mendapatkan bahwa potensi/kapasitas penyuluh BPTP merupakan produk atau luarandari kondisi kerja dan kebijakan yang ada, baik kebijakan internal Badan Penelitian dan PengembanganPertanian/BPTP maupun kebijakan instutusi pertanian terkait di luar Badan Penelitian dan Pengembangan Pertanian.334Jurnal Pengkajian dan Pengembangan Teknologi Pertanian Vol. 8, No.3, Nopember 2005 : 333-351Penyuluh mempunyai persepsi setuju dengan hampir semua hipotesis yang merupakan kendala dalam pelaksanaantugas pokok dan fungsinya. Hal ini mengindikasikan bahwa penyuluh mempunyai persepsi bahwa potensi/kapasitasnya merupakan resultante dari kendala eksternal dan internal di lingkugan kerjanya, yaitu: (a) potensi/kapasitas penyuluh, (b) permasalahan struktural, (c) kinerja fungsional penyuluh, (d) fasilitas kerja dan dukunganadministrasi, dan (e) faktor-faktor eksternal di luar Badan Penelitian dan Pengembangan Pertanian/BPTP. Dengandemikian, upaya peningkatan kinerja penyuluh BPTP perlu didahului dengan implementasi kebijakan dan berbagaikegiatan yang diperlukan dan berkaitan dengan kelima kendala internal dan eksternal tersebut.Kata kunci: penyuluh, alih inovasi, persepsi